PRESCRIBING GENERIC DRUGS: PERCEPTION, OBEDIENCE, AND SUPERVISION AT KALISAT DISTRICT HOSPITAL - Isna Rahmawati; Alief Dyaningayu Savitri (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: The average of generic drugs prescription at Kalisat District Hospital, Jember, in 2009-2011, reached 57.50%, while patent medicine prescription amounted to 42.50%. It showed that the use of generic drugs at Kalisat District Hospital was higher than the use of patent medicine. However, the prescription has not obeyed the service standard with the supposed minimum standard of 90%.Aim: This study aims to determine the doctors’ obedience and their perception toward the supervision of prescribing generic drugs as well as the correlation between doctors’ supervision and obedience in prescribing generic drugs.Methods: This study is a descriptive and observational study by employing a cross-sectional design. This study was conducted starting from April to July 2013 at Kalisat District Hospital, Jember. The samples were 50 prescription documents taken randomly in April 2013. Besides, questionnaires were distributed to 12 doctors in July 2013.Results: The supervision on prescribing generic drugs at Kalisat District Hospital was considered insufficient by the doctors with the percentage of 58.3%. The level of doctors’ obedience in prescribing generic drugs at Kalisat District Hospital reached 68%, while the national standard in April 2013 amounted to 90%. It means that they had not reached the standard of prescribing generic drugs.Conclusion: Based on the cross-tabulation analysis used to investigate the correlation between doctors’ supervision and obedience in prescribing generic drugs at Kalisat District Hospital in July 2013, the results suggested that generic drug supervision correlates with the doctors’ obedience in prescribing generic drugs. The correlation between these two factors is considered moderate. The hospital should increase the supervision of prescribing generic drugs. Thus, doctors should prescribe generic drugs optimally. The hospital management should also perform continuous socialization on the use of generic drugs.Keywords: generic drugs, supervision, obedience, perception.